Distinct gut microbial signature and altered short chain fatty acid metabolism at disease onset in a rat preclinical model of superimposed preeclampsia - Alhasan, Moumen M.; Landa, María S.; García, Silvia I.; Gerlach, Roman; Harb, Hani; Fahlbusch, Fabian B.; Conrad, Melanie L.; Barrientos, Gabriela (Scientific Reports, 2024)
Chronic hypertension is an increasingly prevalent condition that constitutes a risk factor for superimposed preeclampsia during pregnancy. In this study, we assessed the gut microbiome in a rat model of superimposed preeclampsia to characterize the microbial signature associated with defective placentation processes identified at the preclinical disease stage. The blood pressure profile, renal function parameters and fetal phenotype were evaluated in pregnant Stroke-prone Spontaneously Hypertensive Rats (SHRSP) and their normotensive controls. On gestation day (GD)14, feces were collected and gut microbiome composition and short-chain fatty acid concentrations were determined by 16S rRNA sequencing and gas chromatography respectively. At disease onset on GD14, the fecal gut microbiome of SHRSP showed a lower alpha diversity and significant differences in beta diversity when compared with control animals. In the feces, Prevotella, Bifidobacterium, Parasutterella and Roseburia were enriched in SHRSP pregnancies compared to controls, showing a strong correlation with clinical parameters. Bacteria from the families Ruminococcaceae, Oscillospiraceae and the genera Blautia and Faecalibacterium were depleted. Considering short-chain fatty acids, acetate, propionate and valerate were increased in the SHRSP model, showing a strong positive correlation with the relative abundance of enriched taxa. We show that on GD14, at the asymptomatic SPE onset stage, pregnant SHRSP display a distinct gut microbiome signature and altered short chain fatty acid metabolism compared to control animals.
CRIS-Team Scopus Importer:2025-02-04